1994
DOI: 10.1002/jnr.490380604
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglial cyclic AMP response element‐binding protein: A member of the CREB family of transcription factors

Abstract: Several laboratories have shown that cyclic AMP (cAMP) plays an important role in inducing oligodendrocyte differentiation and myelin synthesis. Our previous results have shown that oligodendrocytes contain a nuclear protein that binds to the DNA sequence TGACGTCA or cAMP response element (CRE) known to be involved in the transcriptional regulation of cAMP-responsive genes. In this report the oligodendroglial CRE-binding protein was further identified by using two different antibodies which specifically recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Furthermore, intracerebroventricular administration of IGF-I has shown antidepressant-like behavioral effects with increased serotonin transmissions in rodent models (Hoshaw et al, 2008). CREB is also highly expressed in oligodendrocytes (SatoBigbee and Yu, 1993;Sato-Bigbee et al, 1994). Studies have shown that IGF-I can induce multipotent adult neural progenitor cells to become oligodendrocytes (Hsieh et al, 2004).…”
Section: Antidepressant Treatment May Increase Functioning Of Oligodementioning
confidence: 99%
“…Furthermore, intracerebroventricular administration of IGF-I has shown antidepressant-like behavioral effects with increased serotonin transmissions in rodent models (Hoshaw et al, 2008). CREB is also highly expressed in oligodendrocytes (SatoBigbee and Yu, 1993;Sato-Bigbee et al, 1994). Studies have shown that IGF-I can induce multipotent adult neural progenitor cells to become oligodendrocytes (Hsieh et al, 2004).…”
Section: Antidepressant Treatment May Increase Functioning Of Oligodementioning
confidence: 99%
“…We have previously shown the presence of the transcription factor cAMP response element binding protein (CREB) in oligodendrocytes (Sato-Bigbee and Yu, 1993;Sato-Bigbee et al, 1994). CREB belongs to a family of transcription factors which includes various isoforms of CREB modulator protein (CREM) and activation transcription factors (ATF) (Hai et a]., 1989;Habener, 1990;Lalli and Sassone-Corsi, 1994).…”
Section: Introductionmentioning
confidence: 96%
“…The efficiency of CREB as a transcriptional activator of cAMP responsive genes is modulated by its phosphorylation at serine 133 by CAMP-dependent protein kinase A (PKA) (Yamamoto et al, 1989). Our previous results indicated that the CREB protein present in oligodendrocytes contains the transactivating region designated as the alpha region (Sato-Bigbee et al, 1994). This alpha region, which is absent in the negative regulator CREB-2, interacts with the PKA phosphorylation motif to stimulate transcription .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…cAMP plays an important role in inducing oligodendrocyte differentiation and myelin synthesis (10,11). Furthermore, the transcription factor, cAMP response element-binding protein (CREB) is a key mediator of stimulus-induced cAMPmediated nuclear responses that underlie survival of neurons.…”
mentioning
confidence: 99%